Demography, Breeding Biology and Predation of Willow Ptarmigan at Anderson River Delta, Northwest Territories - Hannon, Susan J.; Barry, Thomas W. (ARCTIC, 1986)
Observations on the willow ptarmigan (Lagopus lagopus albus) were made during the breeding season from 1958 to 1985 at the Anderson River delta, N.W.T. Numbers of territorial males on a 65 ha study area have fluctuated between 7 and 28 over this time, with numbers peaking in 1961-62, 1969 and 1980. Peaks in ptarmigan numbers appear to be fairly synchronous over a large geographical area. Large flocks of males were observed in some years. In 1978, these males, mainly yearlings, had similar wing lengths to, but weighed slightly more than territorial males. There appeared to be shortage of hens in 1978, possibly caused by differential mortality during the winter. Mean clutch size ranged from 8.7 to 10.4 and mean number of fledged chicks per brood ranged from 6.3 to 6.9. Within North America clutch size of willow ptarmigan does not appear to increase with increasing latitude. As in other localities, raptors and foxes appeared to be the main predators of ptarmigan. More males than females were killed on the breeding area, but this could have been because more males were present.Key words: willow ptarmigan, Northwest Territories, breeding, clutch size, demography, predation Mots clés: lagopède des saules, Territoires du Nord-Ouest, nidification, taille de la couvée, démographie, prédation